A proposed methodology for impact assessment of air quality traffic-related measures: The case of PM2.5 in Beijing. (August 2018) - Fontes, Tânia; Li, Peilin; Barros, Nelson; Zhao, Pengjun
Abstract: Air quality traffic-related measures have been implemented worldwide to control the pollution levels of urban areas. Although some of those measures are claiming environmental improvements, few studies have checked their real impact. In fact, quantitative estimates are often focused on reducing emissions, rather than on evaluating the actual measures' effect on air quality. Even when air quality studies are conducted, results are frequently unclear. In order to properly assess the real impact on air quality of traffic-related measures, a statistical method is proposed. The method compares the pollutant concentration levels observed after the implementation of a measure with the concentration values of the previous year. Short- and long-term impact is assessed considering not only their influence on the average pollutant concentration, but also on its maximum level. To control the effect of the main confounding factors, only the days with similar environmental conditions are analysed. The changeability of the key meteorological variables that affect the transport and dispersion of the pollutant studied are used to identify and group the days categorized as similar. Resemblance of the pollutants' concentration of the previous day is also taken into account. The impact of the road traffic measures on the air pollutants' concentration is then checked for those similar days using specific statistical functions. To evaluate the proposed method, the impact on PM2.5 concentrations of two air quality traffic-related measures (M1 and M2) implemented in the city of Beijing are taken into consideration: M1 was implemented in 2009, restricting the circulation of yellow-labelled vehicles, while M2 was implemented in 2014, restricting the circulation of heavy-duty vehicles. To compare the results of each measure, a time-period when these measures were not applied is used as case-control. Graphical abstract: Image 1 Highlights: A method to assess the impact of traffic measures on air quality is proposed. Statistical functions are used to analyse the impact of a traffic measure. Traffic measures are compared for 'similar days'. The impact of two traffic measures implemented in Beijing on PM2.5 are analysed. Abstract : A statistical method to assess the impact of traffic measures on air quality is proposed using days with similar environmental conditions.